Edukasi Pengembangan Produk UMKM dengan Pendekatan Inovasi pada UMKM Kelurahan Curug Kecamatan Bojongsari Depok - Rahmadania, Siti Aisyah Nurrizqi; Putren, Irenne (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving local economies, particularly in urban and semi-urban areas. However, many MSME actors face challenges in product development and innovation due to limited knowledge and resources. This community service activity aims to enhance the capacity of MSME entrepreneurs in Curug Subdistrict, Bojongsari District, Depok City through education on product development with an innovation approach. The program was conducted in April 2025 at the Curug Subdistrict Office and involved 12 lecturers from Pamulang University as facilitators. A total of 28 MSME entrepreneurs from Curug participated in the activity. The implementation method included presentations, practical sessions, discussions, and Q&A. The materials focused on product innovation strategies, value creation, packaging design, and marketing approaches tailored for MSMEs. The interactive format encouraged active participation and knowledge sharing among participants. As a result, participants gained new insights and skills in developing and differentiating their products to enhance market competitiveness. Feedback from attendees indicated increased motivation and readiness to implement innovations in their respective businesses. This PKM activity demonstrated the importance of academic involvement in empowering MSMEs and fostering local economic resilience through practical education and collaborative learning.